MyGamelan : A persuasive mobile application for Malay gamelan music / Madihatul Aqilah Mohd Jamel - Mohd Jamel, Madihatul Aqilah (2017)
Gamelan is one of the traditional music in Malaysia. There are seven gamelan instruments, but this project only focus on one instrument which is bonang. According to the preliminary study, there are a lot of peoples have interest in knowing about gamelan music instrument but there were some limitations to it. In order to learn gamelan music, people need to attend the manual class which is costly and have time constraints. Another limitation would be the gamelan instruments is hard to get due to its own price because it needs to be imported from different country. This project will be focusing on the development of a persuasive mobile application for Malay gamelan music by implementing persuasive design principle. There are six persuasive design elements involved in this project, which are tunneling, tailoring, self-monitoring, contrast, communication framing and multimedia usage. This project use Mobile Application Development Lifecycle (MADLC), which consist of four phase which is planning, designing, developing and testing. The use of persuasive technology in this project shows that the application is useful and satisfy the user when using it. Based on the usability testing result, the satisfaction criteria have the highest value with the average of 4.7. Besides, the application developed is suitable for people who are interested in learning about Malay gamelan music. The application has limitation in terms of platform compatibility and the application does not support a complete gamelan song because the application still need to be enhanced for future use. Due to this limitation, the future works for the application is the application can be supported on different platform such as IOS or windows. Next is the application can show more gamelan song with more challenging level for player. Besides, the application can compare score between player of different smartphone.